2017
DOI: 10.1080/22201181.2017.1321862
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of final-year UKZN medical students about anaesthesia as a specialty choice

Abstract: South Africa suffers from a drastic shortage of anaesthesiologists. This shortage has a major impact on the provision of safe, timeous and appropriate surgery for the population. One factor implicated in this shortage may be the difficulty in appropriate recruitment of trainees. Methods: A questionnaire-based cross-sectional study was conducted among the final-year medical students at the University of KwaZulu-Natal (UKZN), for the year 2013. Results: At total of 112 final-year medical students participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…3,5,6,[11][12][13]16 In addition, studies performed solely among medical students showed that anaesthesiology was infrequently indicated as a career choice, which was attributed to insignificant exposure during undergraduate training. 14,15,17,21,22 Increasing undergraduate exposure to anaesthesiology should be considered to improve the visibility of the discipline among medical students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,6,[11][12][13]16 In addition, studies performed solely among medical students showed that anaesthesiology was infrequently indicated as a career choice, which was attributed to insignificant exposure during undergraduate training. 14,15,17,21,22 Increasing undergraduate exposure to anaesthesiology should be considered to improve the visibility of the discipline among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among medical students in 2017 at a South African university found that anaesthesiology was ranked fourth in popularity as a future career. 17 The study also revealed that increasing exposure to anaesthesiology at an undergraduate level can improve the perceptions of medical students. 17 Another study found that lifestyle factors are important when considering a specialty as a career.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation